Rewriting Scripture in Second Temple Times. By Sidnie White Crawford - Hempel, Charlotte (The journal of theological studies, 2011)
The full publication of the Dead Sea Scrolls has considerably enlarged the corpus of ancient Jewish literature that was au courant among learned Jews in the latter half of the Second Temple period. One area where the Scrolls have offered a plethora of new primary evidence is the corpus of evolving scriptures, their creative transmission, elaboration, and interpretation. Sidnie White Crawford has worked on this material throughout her scholarly career and is therefore admirably equipped to offer an authoritative account of where we are today.